Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.na.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human migration and wealth distribution

Abstract: a b s t r a c tDynamics of human populations depends on various economical and social factors. Their migration is partially determined by the economical conditions and it can also influence these conditions. This work is devoted to the analysis of the interaction of human migration and wealth distribution. The model consists of a system of equations for the population density and for the wealth distribution with conventional diffusion terms and with cross diffusion terms describing human migration determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…The proof is postponed to the Appendix A. Therefore, the randomized dynamic model in Equations (7)- (11) includes three random parameters b = {b 1 , b 2 , b 3 } of the interval type that are defined over the three-dimensional cube with faces (Equations (12) and 13), i.e.,…”
Section: Randomized Model Of Migratory Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proof is postponed to the Appendix A. Therefore, the randomized dynamic model in Equations (7)- (11) includes three random parameters b = {b 1 , b 2 , b 3 } of the interval type that are defined over the three-dimensional cube with faces (Equations (12) and 13), i.e.,…”
Section: Randomized Model Of Migratory Interactionmentioning
confidence: 99%
“…Note that the problem of migration touches upon many aspects of socioeconomic, psychological and political status of the space of migratory movements. Thus, of crucial role is the structural analysis of inter-and intraregional migration flows [4] and motivations that generate them [2,11]. The results of structural and motivational analysis of migratory processes are used for computer simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the problem of migration touches upon many aspects of socioeconomic, psychological and political status of the space of migratory movements. So of crucial role is the structural analysis of inter-and intraregional migration flows [6] and motivations that generate them [7,8]. The results of structural and motivational analysis of migratory processes are used for computer simulation.…”
Section: Introductionmentioning
confidence: 99%
“…A. MOROZOV [22]. Zincenko et al predict scenarios of a sharp population decline and deterioration of the economic situation after some periods of intensive transient growth.…”
mentioning
confidence: 99%
“…The importance of the shape of the functional response in ecological predator-prey models has been previously emphasized [3,6,15]. For example, recent studies revealed the role of herd behaviour and collective defence of animals in dynamics of predator-prey systems: animal aggregation of individuals in herds would reduce their consumption by predators and this can be mathematically described via a square root functional response [22]. In their article, Vilches et al comprehensively explore a predator-prey model with a generic square root functional response [21].…”
mentioning
confidence: 99%